2019
DOI: 10.1016/j.envres.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bisphenol A in children, mothers and fathers from Slovenia: Overall results and determinants of exposure

Abstract: In the present study, urinary bisphenol A (BPA) levels were reported for the first time in the Slovenian general population and were evaluated with regard to dietary and non-dietary exposure sources, and compared according to age, gender and area of residence. First morning urine was collected from children (6-11 years), their mothers (30-52 years) and fathers (30-53 years), living in urban and rural areas of Slovenia. Besides basic questionnaire data on general population characteristics, socio-economic statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 32 publications
3
8
2
1
Order By: Relevance
“…This suggests that even when exposed to the same dose of toxic chemicals, children are more harmed than adults, and therefore TDI research and stricter regulation for children, infants, and neonates are needed [6,12]. In this study, the concentrations of MEP, MnBP, MiBP, and BPA in mothers were significantly correlated with those in infants, similar to those reported previously [8,11,[15][16][17]20]. However, Tratnik et al reported that the urine concentrations of BPA in mother-child pairs were significantly correlated, whereas those between fathers and their children were not correlated [23].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This suggests that even when exposed to the same dose of toxic chemicals, children are more harmed than adults, and therefore TDI research and stricter regulation for children, infants, and neonates are needed [6,12]. In this study, the concentrations of MEP, MnBP, MiBP, and BPA in mothers were significantly correlated with those in infants, similar to those reported previously [8,11,[15][16][17]20]. However, Tratnik et al reported that the urine concentrations of BPA in mother-child pairs were significantly correlated, whereas those between fathers and their children were not correlated [23].…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, the median concentrations of MEP, MiBP, MBzP, MiNP, TCS, MP, and PP were 3.68, 5.68, 0.63, 0.53, 0.24, 4.85, and 0.51 µg/L, respectively, which were lower than the values reported from Denmark, Germany, Greece, Ireland, Japan, Poland, Slovakia, Spain, Sweden, and Taiwan [9,10,[12][13][14][15][16][17][18][19][20][21]. The median concentrations of BPA, MnBP, MEHP, and secondary metabolites of phthalate (MEOHP, MEHHP, MECPP, and MCOP) were slightly lower or higher than the values reported from Greece, Ireland, Japan, Poland, Slovakia, Spain, Sweden, and Taiwan [8][9][10][12][13][14][15][16][17][18][19][20][21][22]. These patterns were similar to the concentrations of these toxic chemicals in infants.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations